Comorbidity of Arithmetic and Reading Disorder: Basic Number Processing and Calculation in Children With Learning Impairments. - Raddatz, Julia; Kuhn, Jörg-Tobias; Holling, Heinz; Moll, Kristina; Dobel, Christian (Journal of Learning Disabilities)
The aim of the present study was to investigate the cognitive profiles of primary school children (age 82-133 months) on a battery of basic number processing and calculation tasks. The sample consisted of four groups matched for age and IQ: arithmetic disorder only (AD; n = 20), reading disorder only (RD; n = 40), a comorbid group (n = 27), and an unimpaired control group (n = 40). Multiple 2 (RD vs. No RD) X 2 (AD vs. No AD) factorial ANCOVAs showed that children with RD had selective impairments in counting and number transcoding efficiency. In contrast, children with AD performed poorly in most tasks, including symbolic and nonsymbolic magnitude comparisons, subitizing, number line estimation, number sets, number transcoding accuracy, and calculation. These findings provide further support that AD is characterized by multiple, heterogeneous underlying deficits. In contrast, RD is associated with specific number processing impairments only if tasks require verbal processing. Taken together, the results fully support the assumption of comorbid additivity of AD and RD.